Administration of Vitamin D3 Improves Hemoglobin Level by Regulating TNF-a and IL-6 in DSS-induced Colitis Mice - Ervin Monica; Primayuni Dhia Hasanah; Arief Fadillah; Rara Aulia; Eko Sulistijono; Satrio Wibowo (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Anemia is frequently found in ulcerative colitis (UC) patients and assumed to be related to inflammatory process. Vitamin D3 (VD) is known to have anti-inflammatory and immunomodulatory effects. It also has the potential to be an alternative treatment of the inflammatory process that occurs at UC, however its mechanism has not been clearly established. This study aimed to assess the effect of VD on histopathology and hemoglobin levels in UC through its regulation in tumor necrosis factor (TNF)-α and interleukin (IL)-6.METHODS: Total samples of 24 mice were divided equally into Sham group, UC group, UC+VD group (given 3% dextran sodium sulfate (DSS) followed by VD), and VD+UC group (given VD followed by 3% DSS). Mouse Colitis Histology Index (MCHI) was used to measure histopathological changes. Immunohistochemical staining was used to observe expression of TNF-α and IL-6 in colon. Evaluation of anemia was determined by hemoglobin levels.RESULTS: Based on MCHI scores, significant epithelial damage was found in colon sample of UC group (8.25±3.05) compared to Sham (0.33±0.26), UC+VD (2.33±1.07), and VD+UC group (2.83±0.75) (p<0.05). Significant lower numbers of TNF-α were found in Sham (27.33±3.42), UC+VD (36.33±1.86), and VD+UC group (36.68±1.86) compared with UC group (44.66±4.87) (p<0.05). Significant less IL-6 expression was found in Sham (18.05±2.96), UC+VD (24.78±0.79), and VD+UC group (25.09±2.79) compared to UC group (38.85±3.51) (p<0.05). Differences in hemoglobin levels were significantly lower in UC group (11.85±0.97) compared to Sham (14.25±0.47), UC+VD (13.68±0.68), VD+UC group (13.52±1.07) (p<0.05).CONCLUSION: VD significantly reduced proinflammatory cytokines, increased mucosal repair, and improved hemoglobin levels.KEYWORDS: colitis, ulcerative, interleukin-6, tumor necrosis factor-alpha